The potential of fibroblast growth factor-21 and adiponectin as diagnostic biomarkers for type 2 diabetes mellitus: differential levels in response to treatments - Madleen Nabeel Al-Qusous; Rami Dwairi; Rasha Mohamed Hussein (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background Diabetes mellitus (DM) is a global epidemic disease affecting millions each year. Recent studies have suggested novel biomarkers that are linked to DM. This study aimed to measure the levels of fibroblast growth factor-21 (FGF-21) and adiponectin in the blood of patients with type 2 DM and to assess the variations in their levels in response to the type of treatments. The possible correlations with several biochemical parameters and the diagnostic potential of FGF-21 and adiponectin as biomarkers for DM were also investigated. Eighty subjects were classified into control, Type 2 DM patients who were treated with metformin, Type 2 DM patients who were treated with metformin + oral hypoglycemic agents (OHAs), and Type 2 DM patients who were treated with insulin + metformin + OHAs. Results The metformin + OHAs group and the insulin + metformin + OHAs group had higher levels of FGF-21 when compared to the control group. The metformin + OHAs also had significantly higher adiponectin levels when compared to the control or metformin groups. The serum levels of FGF-21 in the diabetic subjects were negatively correlated with LDL, direct bilirubin, albumin, and insulin levels and positively correlated with the duration of DM. However, the serum levels of adiponectin in the diabetic subjects were negatively correlated with weight while positively correlated with potassium levels. Remarkably, FGF-21 and adiponectin were effective biomarkers for diagnosing DM with a specificity of 100% and 90% and sensitivity of 52.3% and 64.5%, respectively. Conclusion These findings suggest that FGF-21 and adiponectin play crucial roles in DM diagnosis and prognosis and that their levels change depending on the treatment type.